PERBEDAAN PEMBELAJARAN JIGSAW DAN DISKUSI PRESENTASI TERHADAP HASIL BELAJAR IPA BIOLOGI SISWA KELAS VIII SMP MUHAMMADIYAH 4 SURAKARTA SEMESTER GENAP TAHUN AJARAN 2015/2016 - PURBOWATI, LUSIA WAHYU; Anif, M.Si, Dr. Sofyan (2016)
The aims of study to discover the difference of jigsaw learning and presentation discuss to ward result of learning Biology sains of eight grade students Yunior High School in Muhammadiyah 4 Surakarta at even semester of 2015/2016 year. The research used true experiment method with posttest only control group desaign. Research population was class VIII Student. Sample consist of three class choised with random sampling. The result data with observation, documentation and post test, the data analysis used one way anava. Before analysis of data did analyzes, prerequnsite test is normality and homogeneity test. The presentation discus learning the result have average 76,7 and jigsaw leraning 60,7 and in control learning 48,7. The final result shows....the difference of jigsaw learning and presentation discuss to ward result of learning Biology sains of eight grade students Yunior High School in Muhammadiyah 4 Surakarta at even semester of 2015/2016 year.s